Sunset Boulevard from movie to musical - Lloyd Webber, Andrew 1948- (Holt, 1993)
This lavishly illustrated, definitive account traces the origins of the film and tells the fascinating story of the making of Lloyd Webber's latest masterpiece
Keywords: Lloyd Webber, Andrew <1948-> -- Sunset Boulevard; Lloyd Webber, Andrew -- 1948- -- Sunset Boulevard; Sunset Blvd. (Motion picture); Sunset Boulevard -- Film; Musicals -- Librettos; Bildband